Beyond Management and the Worker: The Institutional Function of Management - Pfeffer, Jeffrey (Academy of Management Review, 1976)
Management's role in negotiating the organization's relationships with the environment has been neglected in theory and research. Strategies for managing interorganizational interdependence include: merger, joint ventures, cooptation, movement of personnel among organizations, regulation, and political activity. Institutional management activities can be explained using variables measuring dimensions of the organization's context.